Case report: Autoimmune glial fibrillary acidic protein astrocytopathy misdiagnosed as tuberculous meningitis - Qin, Ningxiang; Wu, Xingguo; Wang, Jing; Wang, Wei; Wang, Xuefeng; Ma, Yuanlin; Wang, Liang (Frontiers in Neurology, 2023)
Background：Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a new form of autoimmunity-mediated central nervous system disease that mostly affects the meninges, brain, spinal cord, and optic nerve. When patients exhibit meningoencephalitis, it is easily confused with infectious meningoencephalitis; When cerebrospinal fluid (CSF) performance is similar to that of tuberculous meningitis (TBM), it is particularly easy for the diagnosis to be confused with TBM. Methods：Herein, we retrospectively analyzed five cases of autoimmune GFAP astrocytopathy, which initially were misdiagnosed as TBM. Results：It is difficult to distinguish between the disorders when there is no direct evidence of antibody detection or tuberculosis. An antibody detection completed can make the definite diagnosis. Conclusion：It is difficult to distinguish between the disorders when there is no direct evidence of antibody detection or tuberculosis. When the patient's clinical symptoms and routine biochemical examination in the CSF are similar to TBM, and if other examinations related to tuberculosis are negative and there are nonspecific changes in imaging and EEG, it is necessary to consider whether there is the possibility of autoimmune GFAP astrocytopathy and to complete the antibody detection to make a definite diagnosis in a timely manner.